PGC1α −1 Nucleosome Position and Splice Variant Expression and Cardiovascular Disease Risk in Overweight and Obese Individuals - Tara M. Henagan; Laura K. Stewart; Laura A. Forney; Lauren M. Sparks; Neil Johannsen; Timothy S. Church (PPAR Research)
PGC1α, a transcriptional coactivator, interacts with PPARs and others to regulate skeletal muscle metabolism. PGC1α undergoes splicing to produce several mRNA variants, with the NTPGC1α variant having a similar biological function to the full length PGC1α (FLPGC1α). CVD is associated with obesity and T2D and a lower percentage of type 1 oxidative fibers and impaired mitochondrial function in skeletal muscle, characteristics determined by PGC1α expression. PGC1α expression is epigenetically regulated in skeletal muscle to determine mitochondrial adaptations, and epigenetic modifications may regulate mRNA splicing. We report in this paper that skeletal muscle PGC1α  −1 nucleosome (−1N) position is associated with splice variant NTPGC1α but not FLPGC1α expression. Division of participants based on the −1N position revealed that those individuals with a −1N phased further upstream from the transcriptional start site (UP) expressed lower levels of NTPGC1α than those with the −1N more proximal to TSS (DN). UP showed an increase in body fat percentage and serum total and LDL cholesterol. These findings suggest that the −1N may be a potential epigenetic regulator of NTPGC1α splice variant expression, and −1N position and NTPGC1α variant expression in skeletal muscle are linked to CVD risk. This trial is registered with clinicaltrials.gov, identifier NCT00458133.